Transparency and accuracy in funding investigator-initiated clinical trials: a systematic search in clinical trials databases. Issue 5 (14th May 2019) - Madeira, Catarina; Santos, Francisco; Kubiak, Christine; Demotes, Jacques; Monteiro, Emília Carreira
Abstract : Objectives: This study aims to identify the sources of funding for investigator-initiated clinical trials (IICTs) in Portugal, and to recommend ways to improve the quality of information collected from clinical trial databases about funding. Design and methods: A systematic search of trial registrations over the last 13 years—using the WHO International Clinical Trials Registry Platform (WHO-ICTRP) and four clinical trials registries (CTRs)—was carried out to identify IICTs in Portugal, used as a case study. Data from the databases were compared with data contained in publications to evaluate the consistency of information on funding sources. The term 'database' is used in this study to refer to both the WHO-ICTRP and the CTRs. When mentioned separately, the WHO-ICTRP is referred to as a 'platform', while the CTRs are referred to as 'registries'. Outcome: Suggestions to improve clinical trials databases to clearly identify the funding sources and data ownership in IICTs. Results: Two hundred and eighty-two IICTs were identified in Portugal. Twenty per cent of trials were supported by industry with unclear information on the ownership of the results. Inaccuracy was found in the information about sponsors and funders. The information about funding in all resulting publications (77 out of 133 completed studies) was also inconsistent between databases in 35 out of 77 (45%) of the studies. Notably, 23% of the trials funded by non-profit organisations (n=226) received funds from international and/or national funding agencies. Conclusions: Identification of IICT funding and ownership of results is unclear in the databases used for this study, which may lead to misunderstandings about the independence of the obtained results. Transparency and accuracy are desirable so that public decision makers and strategic partners can accurately evaluate national performance in this particular type of clinical research.